Preoperative process’ framework of patients with breast câncer in the pandemic by COVID-19 (Research, Society and Development, 2022)
This study aimed to analyze the care processes framework for breast cancer patients undergoing adjuvant oncologic surgery during the pandemic by COVID-19. Descriptive, retrospective study, having as scenario a reference oncologic hospital in Rio de Janeiro - Brazil. Carried out a documentary analysis of 95 patients with breast cancer during June 2020. The results show a framework composed of ten steps ranging from screening by mastology to the outcome of breast surgery. It is concluded that the framework was a strategy to minimize risks related to the surgical process of patients with breast cancer and that for cases of tests suggestive of infection by COVID-19 there was a need for repetition of some care processes.